Juridical Analysis of Crypto Assets as Property in Indonesian - Kirana, Kimmy Baby; Urbanisasi, Urbanisasi (CV. Publikasi Indonesia, 2025)
The development of technology and digitalization has brought significant changes to various aspects of life, including the financial sector. One of the key innovations is crypto assets, which are digital assets utilizing cryptographic technology and blockchain for transaction security and verification. These assets have become a global phenomenon, attracting attention from the public, market participants, and regulators, including in Indonesia. This study aims to analyze the legal status of crypto assets as property under Indonesian Civil Law. The rapid development of cryptocurrency and digital assets has raised questions regarding their classification as property and how they should be treated within existing legal frameworks. This research examines whether crypto assets can be considered as movable property under the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata) and explores the implications of this classification on property rights, transactions, and legal protections. Through a juridical analysis, this paper investigates the legal challenges and opportunities presented by crypto assets, particularly considering the legal void in Indonesian legislation regarding digital assets. The study concludes that, while crypto assets are not explicitly regulated under current Indonesian Civil Law, they may be categorized as movable property with certain legal considerations, especially in terms of ownership, transfer, and dispute resolution.